Finite Element Analysis on Cube and Cylinder Model of Ceramic Waste Concrete - Zamri, Muhammad Iqbal; Wan Amizah Binti Wan Jusoh; Mohamad Hairi Bin Osman (Progress in Engineering Application and Technology, 2021)
The ceramic industry is considered to produce a massive volume of ceramic waste per year, and most of it is found in landfills. The reuse of such wastes in concrete may be a win-win scenario. This paper focuses on the adaptation of ceramic waste as the partial replacement as a coarse aggregate in the concrete mixture. This study is to determine the performance of concrete compression behavior whether the waste material that replaces natural coarse aggregates are performed to compare with the ordinary concrete. The proportion of the replacement material in this study was 0%, 20%, 40% and 60%. There are two models created in this study, which are the concrete cube and concrete cylinder, with the size of specimen concrete cube 150mm x 150mm x 150mm while concrete cylinder 0.15m x 0.30m. Data from the previous study was used such as concrete density, modulus elasticity and Poisson ratio to assign in the Finite Element Model. This result is to indicates the stress and strain and also deformation of displacement of concrete mix with ceramic waste and the strength of concrete that increased with the addition of ceramic waste, compared to the conventional concrete strength. The result from the Abaqus simulation states that ceramic waste concrete at 40% produces the best performance of compressive strength.